2020
DOI: 10.2147/dddt.s247947
|View full text |Cite
|
Sign up to set email alerts
|

<p>Protective Effects of Crocetin on Arsenic Trioxide-Induced Hepatic Injury: Involvement of Suppression in Oxidative Stress and Inflammation Through Activation of Nrf2 Signaling Pathway in Rats</p>

Abstract: Arsenic trioxide (ATO) has been shown to induce hepatic injury. Crocetin is a primary constituent of saffron, which has been verified to have antioxidant and antiinflammatory effects. In the current experiment, we evaluated the efficacy of crocetin against ATO-induced hepatic injury and explored the potential molecular mechanisms in rats. Methods: Rats were pretreated with 25 or 50 mg/kg crocetin 6 h prior to treating with 5 mg/ kg ATO to induce hepatic injury daily for 7 days. Results: Treatment with crocetin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 43 publications
4
6
0
Order By: Relevance
“…Dangerously, H 2 O 2 and O 2− have the potential to produce highly unstable and toxic hydroxyl radicals (OH − ) in the iron-catalyzed Haber-Weiss reaction ( 5 ). High levels of ROS not only stimulate cell membrane lipid peroxidation, causing oxidative damage to mitochondria and cell membranes in cardiomyocytes, but also activate nuclear transcription factor damage and upregulate expression factors of inflammation ( 6 ). Severe oxidative stress can regulate B-cell lymphoma-2 (BCL-2) and BCL2-associated X (BAX) in mitochondria, and finally activate Caspase-3 (CASP3) to induce apoptosis ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Dangerously, H 2 O 2 and O 2− have the potential to produce highly unstable and toxic hydroxyl radicals (OH − ) in the iron-catalyzed Haber-Weiss reaction ( 5 ). High levels of ROS not only stimulate cell membrane lipid peroxidation, causing oxidative damage to mitochondria and cell membranes in cardiomyocytes, but also activate nuclear transcription factor damage and upregulate expression factors of inflammation ( 6 ). Severe oxidative stress can regulate B-cell lymphoma-2 (BCL-2) and BCL2-associated X (BAX) in mitochondria, and finally activate Caspase-3 (CASP3) to induce apoptosis ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Dihydroethidium (DHE) staining was performed according to the manufacturer’s protocols ( Liu et al, 2020 ). In brief, 8 μm-thick frozen left ventricular sections were incubated with DHE solution (Servicebio, Wuhan, China) for 30 min at 37°C, and then the sections were viewed under a fluorescence microscope (Leica, Wetzlar, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…An increasing number of studies have consistently shown that ATO is effective against other cancer types, including hepatocellular carcinoma, pancreatic cancer and lung cancer (9,10). In past decades, clinical data have shown that excessive use of ATO causes hepatotoxicity, nephrotoxicity and cardiotoxicity (11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%